STRATEGI PEMASARAN PELAYANAN RAWAT JALAN EKSEKUTIF (POLIKLINIK NUSA INDAH) RSUD TUGUREJO SEMARANG - Fila Mulia Citra Permata Abadi; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
Tugurejo Regional General Hospital has an executive outpatient service called Poliklinik Nusa Indah. Where one mission RSUD Tugurejo is to develop excellent service. Based on the above, it is necessary to plan the marketing strategy to improve the utilization of outpatient services. The purpose of this research is to analyze marketing strategy of outpatient service of RSUD Tugurejo Semarang. The type of research used is Exploratory Research with qualitative approach. Data collection using indepth interview method and secondary data with main informant were 5 people and 2 triangulation informant. From research result based on IFE and EFE matrix it is known that Tugurejo Hospital outpatient service is in quadrant I is asgresive strategy, which is a very favorable situation for RSUD Tugurejo especially on executive outpatient service because it has opportunity and strength that can be utilized. The strategy to be used in this condition is to support an aggressive growth policy (growth-oriented strategy). The SWOT matrix alternative strategy is to conduct periodic promotions to private agencies or companies, manufacture and distribute executive outpatient leaflets, conduct marketing planning by looking at the marketing mix, optimizing physician on call systems, improving facilities and service quality, opening access to services for participants BPJS, and evaluate marketing activities. Based on the results of the QSPM Matrix the main marketing strategy that can be applied is to conduct regular promotions to private agencies or companies. Suggestions in this study are to increase cooperation with private agencies, make executive outpatient leaflets, optimize on-call doctor systems, and open access for BPJS participants.